Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 11 - Rational Expressions and Functions - 11-5 Solving Rational Equations - Practice and Problem-Solving Exercises - Page 683: 22



Work Step by Step

Given: $z^2-(z+2)=z(z+2)$ $z^2-z-2=z^2+2z$ $\implies z^2-z^2-2z-z-2=0$ $\implies -3z-2=0$ $\implies 3z+2=0$ or, $3z=-2 \implies z=-\frac{2}{3}$ $\implies z=-\frac{2}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.